2017
DOI: 10.1111/spc3.12363
|View full text |Cite
|
Sign up to set email alerts
|

Culture and attention: Recent empirical findings and new directions in cultural psychology

Abstract: Over the past 3 decades, cultural psychologists have empirically investigated the influence of cultural meaning systems on human psychology. Under the rubric of holistic versus analytic thought, researchers have demonstrated that there are substantial cultural variations in social cognition, and that such variations are observable even in so-called fundamental psychological processes, such as attention. The aim of this paper is to review 3 major themes in culture and attention: (1) culture and attention to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 122 publications
(180 reference statements)
5
28
0
Order By: Relevance
“…Although context-dependent judgments were made in both countries, the influence of verbal vignettes describing polite situations was stronger in Japan than the UK, with the effect of vignettes describing happy contexts being comparable in the two countries. This result is generally consistent with the notion of analytic versus holistic thinking styles (Masuda 2017). While the former (dominant in the Western world) is selectively focused on central objects or targets rather than the surroundings, holistic thinking (dominant among East Asians) emphasises a context-oriented focus of perception (Ma-Kellams 2014).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although context-dependent judgments were made in both countries, the influence of verbal vignettes describing polite situations was stronger in Japan than the UK, with the effect of vignettes describing happy contexts being comparable in the two countries. This result is generally consistent with the notion of analytic versus holistic thinking styles (Masuda 2017). While the former (dominant in the Western world) is selectively focused on central objects or targets rather than the surroundings, holistic thinking (dominant among East Asians) emphasises a context-oriented focus of perception (Ma-Kellams 2014).…”
Section: Discussionsupporting
confidence: 81%
“…The presence of brief descriptions of situations associated with happiness or the need to be polite made the smiles appear more or less genuine compared to smiles presented without any contextual information. Whereas existing research suggests that observers from Eastern cultures may generally rely on the situational context more than Western observers (Masuda 2017;Matsumoto et al 2010), we obtained a similar pattern of findings among British and Japanese participants. The main difference between the two samples, accounting for a significant interaction effect, was due to a stronger influence of the polite vignettes in the Japanese sample than the British sample.…”
Section: Resultssupporting
confidence: 76%
“…Furthermore, a broad array of visual attention processes have been shown to vary with culture, such as patterns of eye movements, the way in which individuals describe and remember scenes, as well as rates of change detection and change blindness (e.g. Boland, Chua, & Nisbett, 2008;Chua et al, 2005;Boduroglu & Shah, 2017;Goh et al, 2007;Ketay et al, 2009;Masuda, 2017;Masuda et al, 2019;Nisbett, 2003;Nisbett & Masuda, 2003;Nisbett & Miyamoto, 2005;Senzaki, Masuda, & Nand, 2014).…”
Section: Culture and Attention Spreadmentioning
confidence: 99%
“…Over the past two decades, an accumulating body of research has demonstrated that there are cultural differences in cognitive processes (e.g. Boduroglu & Shah, 2017;Goh et al, 2007;Ketay, Aron, & Hedden, 2009;Masuda, 2017;Masuda, Li, Russell, Lee, 2019;Nisbett & Masuda, 2003;Nisbett & Miyamoto, 2005). For example, Kitayama (1991, 2010) proposed that cultural variation in self-concept might CULTURE AND ATTENTION DISTRIBUTION 5 influence cognition.…”
mentioning
confidence: 99%
“…The theory of analytic and holistic (A/H) cognition postulates the existence of distinct cognitive and perceptual styles -relatively stable ways of cognitive processing (for review, see Masuda, 2017;Nisbett & Masuda, 2003;Nisbett & Miyamoto, 2005;Nisbett, Peng, Choi, & Norenzayan, 2001). The majority of research in this field focuses on comparing the charac-teristics of cognitive processes in two world regions: the "West" (e.g., North America, Western Europe) and the "East" (mainly the countries of East and Southeast Asia such as China, Japan, South Korea, etc.…”
Section: Introductionmentioning
confidence: 99%